STRUCTURE ACTIVITY RELATIONSHIPS OF DERMATAN SULFATE : EFFECT OF MOLECULAR SIZE AND CARBOXYL GROUP ESTERIFICATION ON HEPARIN C0FACT0R-II ACTIVATION - Mardiguian, J; Corgier, M; Jouany, M (Thrombosis and Haemostasis, 1987)
Dermatan is a high molecular weight glycosaminoglycan which has been shown to enhance the inhibition of thrombin by heparin-cofactor II. The aim of this study was to establish the influence of the molecular size and the role of the carboxyl group on the in vitro activity of Dermatan Sulfate. Pig skin Dermatan Sulfate was fractionated according to molecular size by gel-chromatography on Ultrogel Ac 44. Each fraction was characterized by its sulfur content and by its mean molecular weight measured on a TSK - 4000 column in reference to standard heparin fractions. Methyl esters of the unfractionated Dermatan Sulfate with varying degree of esterification, where prepared via activation of the carboxyl groups with a carbodiimide and reaction with methanol. The results of this study show that the heparin - cofactor II mediated anti-thrombin activity of Dermatan Sulfate is increasing with the molecular weight and is abolished by esterification of the carboxyl groups. Moreover, it can be speculated that each fraction contains the same amount of high affinity fraction and that, like heparin, the potency of the high affinity component is increasing with the molecular weight.